Induced spawning of African catfish (Clarias gariepinus) using goat (Capra aegagrushircus) and pig (Sus scrofa domesticus) pituitary extracts - Jemuel S. Doctolero; Danica S. Sotero; Lorenz J. Fajardo (Journal of Fisheries, 2022)
Concerns relating to cost and availability have directed traditional farmers to expand options on the induced spawning of fish for viable production of seeds. The study was conducted to examine the potential of using pituitary extracts (PE) from goat (Capra aegagrushircus) and pig (Sus scrofa domesticus) on the induced spawning of African catfish (Clarias gariepinus). Pituitary extract of African catfish using 4 mgkg–1 body weight dosage (control) and PE from goat and pig using 4 mgkg–1 and 200 mgkg–1 body weight dosages were single intramuscularly injected to female breeders. Utilisation of goat and pig PE has successfully induced the spawning of African catfish. All female breeders attained ovulation within 10-12 h which is under the prescribed latency period. Total number of eggs spawned ranged from 36200-67600. The three PE used attained comparable result in terms of relative fecundity. Fertilisation rate revealed that PE from goat at 4 mgkg–1 dosage attained similar result to that of control treatment. Hatching period occurred within 24–36 h and goat PE using both dosages gave the highest results in hatching rate. The current study provides preliminary information on the success of using PE from goat and pig for the induced spawning of African catfish.